Deleuze and Guattari : a psychoanalytic itinerary - Abou-Rihan, Fadi (Continuum studies in continental philosophy., 2008)
Shows that, as much as it is an insightful critique of the assimilationist vein in psychoanalysis, "Anti-Oedipus" remains fully committed to Freud's most singular discovery of an unconscious that is procedural and dynamic.